Glucose potentiates β‐cell function by inducing Tphl expression in rat islets. Issue 12 (9th August 2017) - Zhang, Yuqing; Deng, Ruyuan; Yang, Xue; Xu, Wan; Liu, Yun; Li, Fengying; Zhang, Juan; Tang, Hongju; Ji, Xueying; Bi, Yufang; Wang, Xiao; Zhou, Libin; et al.
ABSTRACT: Impaired pancreatic β‐cell function is the primary defect in type 2 diabetes. Glucose is an important regulator of β‐cell growth and function; however, the mechanisms that are involved in the chronic adaptation of β cells to hyperglycemia remain largely unknown. In the present study, global gene expression patterns revealed that tryptophan hydroxylase 1 ( Tph1 ) was the most profound of genes that are up‐regulated in rat islets exposed to high glucose. Calcium and cAMP signals synergistically mediated glucose‐stimulated Tph1 transcription in β cells by activating cAMP‐responsive element‐binding protein and promoting its binding with a Tph1 promoter. Similar to in vitro results, in vivo infusion of high glucose also strongly induced Tph1 expression and serotonin production in rat islets, along with enhanced islet function. Inhibition or knockdown of Tph1 markedly decreased glucose‐potentiated insulin secretion. In contrast, overexpression of Tph1 augmented glucose‐stimulated insulin secretion in rat islets by up‐regulating the expression of genes that are related to islet function. In addition, the long‐acting glucagon‐like peptide 1 receptor agonist, exendin‐4, stimulated Tph1 expression in a glucose‐dependent manner. Knockdown of Tph1 inhibited exendin‐4‐potentiated insulin secretion in rat islets. These findings suggest that Tph1 mediates the compensation of islet function induced by glucose, and that promoting Tph1 expression in pancreatic β cells will provide a new strategy for the treatment of type 2 diabetes mellitus.—Zhang, Y., Deng, R., Yang, X., Xu, W., Liu, Y., Li, F., Zhang, J., Tang, H., Ji, X., Bi, Y., Wang, X., Zhou, L., Ning, G. Glucose potentiates β‐cell function by inducing Tphl expression in rat islets. FASEB J. 31, 5342‐5355 (2017). www.fasebj.org